PENINGKATAN HASIL BELAJAR MAHASISWA MENGGUNAKAN MODEL PERKULIAHAN PROBLEM BASED INSTRUCTION (PBI) MATA KULIAH GAMBAR TEKNIK - Supri adi; Meiyaldi Eka Putra; Fajar Maulana; Ramanda Rizky; Islami Fatwa (JURNAL PENDIDIKAN TEKNIK MESIN, 2023)
This research is motivated by the problem of Engineering Drawing Lectures which are still focused on lecturers, student knowledge about Engineering Drawings is still low because many student learning outcomes do not meet the criteria. Therefore, it is necessary to apply the lecture model so that Engineering Drawing lectures can increase. The model applied is Problem Based Instruction. The purpose of this study was to improve student learning outcomes in the first semester of Engineering Drawing courses. This type of research is Quasi Experimental with one group pretest-posttest design. The subjects in this study were first semester students of the Automotive Technology Vocational Education Study Program at Lancang Kuning University who were enrolled in the 2022/2023 academic year as many as 32 students. Collecting data in this study using pretest and posttest learning outcomes. Data were analyzed using Gain Score. Based on the research results, the average pretest score was 65.75 and the posttest score was 86.50. From the calculation of the Gain Score <g> is 0.557 in the medium category using the Problem Based Instruction (PBI) lecture model for the Engineering Drawing course in the Automotive Technology Vocational Education Study Program, Lancang Kuning University.